Variation in Middle Stone Age mandibular molar enamel-dentine junction topography at Klasies River Main Site assessed by diffeomorphic surface matching. Issue 161 (December 2021) - Grine, Frederick E.; Gonzalvo, Elsa; Rossouw, Lloyd; Holt, Sharon; Black, Wendy; Braga, José
Abstract: The morphology and variability of the Middle Stone Age (MSA) hominin fossils from Klasies River Main Site have been the focus of investigation for more than four decades. The mandibular remains have figured prominently in discussions relating to robusticity, size dimorphism, and symphyseal morphology. Variation in corpus size between the robust SAM-AP 6223 and the diminutive SAM-AP 6225 mandibles is particularly impressive, and the difference between the buccolingual diameters of their M2 s significantly exceeds recent human sample variation. SAM-AP 6223 and SAM-AP 6225 are the only Klasies specimens with homologous teeth (M2 and M3 ) that permit comparisons of crown morphology. While the differences in dental trait expression at the outer enamel surfaces of these molars are slight, diffeomorphic surface analyses of their underlying enamel-dentine junction (EDJ) topographies reveal differences that are well beyond the means of pairwise differences among comparative samples of Later Stone Age (LSA) Khoesan and recent African homologues. The EDJs of both SAM-AP 6225 molars and the SAM-AP 6223 M3 fall outside the envelopes that define the morphospace of these two samples. Although the radiocarbon dated LSA individuals examined here differ by a maximum of some 7000 years, and the two Klasies jaws may differ by perhaps as much as 18, 000 years, it is difficult to ascribe their differences to time alone. With reference to the morphoscopic traits by which the SAM-AP 6223 and SAM-AP 6225 EDJs differ, the most striking is the expression of the protoconid cingulum. This is very weakly developed on the SAM-AP 6223 molars and distinct in SAM-AP 6225. As such, this diminutive fossil exhibits a more pronounced manifestation of what is likely a plesiomorphic feature, thus adding to the morphological mosaicism that is evident in the Klasies hominin assemblage. Several possible explanations for the variation and mosaicism in this MSA sample are discussed. Highlights: Variability of Middle Stone Age human fossils from Klasies is a point of discussion. Some Klasies MSA jaws have a distinct chin, and others have a vertical symphysis. We examined the EDJ topography of Klasies lower molars using diffeomorphism. Differences in EDJ surfaces between Klasies molars exceed Holocene human variation. EDJ morphology adds to the features that differentiate Klasies from Holocene humans.